Tjokro-[ism] Case Study: Reconciling the Tangled-Thread of Cash Management Practice in Treasury Accounting Field - Ria Dewi Ambarwati; Resi Ariyasa Qadri; Miftahul Hadi (Jurnal Riset Akuntansi Terpadu, 2021)
Tjokroaminoto's thought is used in this qualitative case study research to uncover the complexities of cash reconciliation practices for the preparation of the central government's financial statements and identify what went wrong in the practice so that appropriate recommendations can be formulated to overcome these problems. The audit result on LKPP 2018 and 2017 showed problems in the management and recording of cash, inventories, fixed assets, and intangible assets. These problems have impacts on the reliability of financial statements. Optimization of reconciliation to ensure reliability in the preparation of financial statements is questioned. The research results indicate several problems, namely lack of coordination, lack of knowledge, non-compliance, application, and less effective sanctions. This study formulates three recommendations for the government as research implications: increasing knowledge, developing integrated applications, and automating the imposition of sanctions.